A Novel wx2 Gene of Toxoplasma gondii Inhibits the Parasitic Invasion and Proliferation in vitro and Attenuates Virulence in vivo via Immune Response Modulation - Ma, Zhenrong; Yan, Kang; Jiang, Ruolan; Guan, Jie; Yang, Linfei; Huang, Yehong; Lu, Bin; Li, Xuanwu; Zhang, Jie; Chang, Yunfeng; Wu, Xiang (Frontiers in Microbiology, 2020)
Toxoplasma gondii (T. gondii) is an obligate intracellular apicomplexan protozoan that can parasitize most warm-blooded animal and cause severe diseases in immunocompromised individuals or fetal abnormalities in pregnant woman. The treatment of toxoplamosis has been limited by effective drugs. Our previous work indicated that the novel gene wx2 of T. gondii may serve as a candidate vaccinating antigen. Herein, to further investigate the molecular functions of wx2 in highly virulent T. gondii (RH strain), a wx2 gene deletion mutant RH strain (KO-wx2) was established using CRISPR-Cas9. The phynotype of KO-wx2 was analyzed by plaque, invasion, and replication assays in vitro as well as in vivo virulence assays. The results indicated that the targeted deletion of wx2 gene significantly inhibites in vitro parasite growth and replication in the host cells and attenuated parasite virulence in the mouse model. Notably, the percentage of pro-inflammatory factors of interferon gamma (IFN-γ)and interlukin-17A (IL-17A) and anti-inflammatory factor of interlukin-10 (IL-10)in the lymph nodes were up-regulated in mice infected with KO-wx2 strain. Our data suggested that wx2 gene plays an important role in the process of the parasite life cycle and virulence in mice, in addition, also for the immunity reaction with host mainly via Th1 and Th17 cellular immunity not Th2 and Treg.